Customer involvement in greening the supply chain: An interpretive structural modeling methodology - Sanjay Kumar; Sunil Luthra; Abid Haleem (Journal of Industrial Engineering International, 2013)
The role of customers in green supply chain management needs to be identified and recognized as an important research area. This paper is an attempt to explore the involvement aspect of customers towards greening of the supply chain (SC). An empirical research approach has been used to collect primary data to rank different variables for effective customer involvement in green concept implementation in SC. An interpretive structural-based model has been presented, and variables have been classified using matrice d'impacts croises-multiplication appliqué a un classement analysis. Contextual relationships among variables have been established using experts' opinions. The research may help practicing managers to understand the interaction among variables affecting customer involvement. Further, this understanding may be helpful in framing the policies and strategies to green SC. Analyzing interaction among variables for effective customer involvement in greening SC to develop the structural model in the Indian perspective is an effort towards promoting environment consciousness.
Keywords: 650; supply chain; green supply chain management; green distribution; interpretive structural modeling (ISM); MICMAC analysis